Bone-promoting antibacterial biological functional material and preparation method thereof
Nickel-titanium alloy materials prepared by femtosecond laser and anodization technology combined with the loading of nanosilver, solved the problems of bone integration and bacterial infection of bone implants, and achieved good bone binding ability, bone promotion growth ability and antibacterial ability.
Patent Information
- Application Number
- CN202411444106.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Bone implants have problems of poor bone integration and bacterial infection in bone defect repair and bone disease treatment, which affects its long-term stability and therapeutic effect.
Femtosecond laser technology and anodization technology were used to prepare a trench-micro-microporous three-stage micro-nano composite structure of nickel-titanium alloy material, and nanosilver is loaded on its surface to form an antibacterial biological functional material.
This material can significantly improve the bone integration performance and antibacterial ability of bone implants, and promote the regeneration of bone tissue, solving the problems of poor bone integration and bacterial infection.
Smart Images

Figure CN119530798A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a bone-promoting antibacterial biological functional material and a preparation method thereof, and belongs to the technical field of laser application. Background Art
[0002] Bone implants play a vital role in bone defect repair and bone disease treatment. However, the long-term stability and therapeutic effect of bone implants are seriously affected by problems such as poor bone integration and bacterial infection. Poor bone integration results in insufficient bonding between the implant and the surrounding bone tissue, leading to implant loosening, displacement and even surgical failure. On the other hand, bacterial infection is one of the common complications in the clinical application of bone implants, which may cause inflammatory response and bone resorption of the tissue around the implant, seriously affecting the long-term stability of the implant and the patient's therapeutic effect. Therefore, solving the problems of poor bone integration and bacterial infection is crucial to improving the biocompatibility of bone implants, promoting bone tissue regeneration and improving clinical treatment effects.
[0003] The surface morphology and chemical properties of bone implants are crucial to their integration with surrounding bone tissue. Femtosecond laser technology uses ultrashort pulse lasers to regulate the structure of the implant surface at the micron and nanometer levels. It can increase its surface roughness and specific surface area, thereby improving its biocompatibility and cell adhesion. In addition, femtosecond lasers can also induce surface chemical reactions, such as oxidation and carbonization, to further improve the chemical properties of the implant, which is beneficial to the growth of bone cells and the regeneration of bone tissue. Anodizing technology increases its surface roughness, bioactivity and biocompatibility by forming a dense oxide layer on the surface of the implant, which is beneficial to the attachment and growth of bone cells and can promote the formation and regeneration of bone tissue. As surface treatment methods, femtosecond laser technology and anodizing technology can effectively improve the surface morphology and surface properties of implants, thereby promoting the attachment and growth of bone cells and improving the bone integration performance of implants, and have received increasing attention.
[0004] In current research, for example, Mengxia Peng et al. have improved the antibacterial properties of biometallic materials by double surface modification treatments of anodization and preparation of nanosilver coatings, but they focused on the antibacterial properties of the materials and did not pay attention to the osteogenic properties of the materials. Su Wang et al. used femtosecond laser to modify the surface of titanium alloy bone scaffolds, making the surface morphology of the bone scaffolds present a micro-nano morphology, improving its surface roughness, and significantly enhancing the surface activity of the bone scaffolds and their ability to integrate with surrounding bone tissues, but they focused on the osteogenic properties of the materials and did not pay attention to the anti-bacterial infection function of the materials. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of poor bone integration and bacterial infection in the application of bone implants in bone defect repair and bone disease treatment, and to provide a bone-promoting antibacterial biofunctional material and a preparation method thereof; the method ultrasonically treats and dries the polished nickel-titanium alloy material, and uses femtosecond laser direct writing technology to prepare a self-organized composite periodic micro-ripple groove structure by synergistically regulating processing parameters such as laser flux, processing translation stage movement speed and scanning spacing in the processing process; then the material is anodized to form abundant nanopores on the basis of the structure, and a groove-micro-ripple-micropore three-level micro-nano composite structure is prepared; then, the prepared three-level micro-nano composite structure is placed in an alkaline Tris buffer containing dopamine hydrochloride to be coated with a polydopamine coating; then, the groove-micro-ripple-micropore three-level micro-nano composite structure coated with the polydopamine coating is placed in a silver nitrate solution to load nanosilver on its surface, and finally a biofunctional material with good bone bonding ability, bone growth promotion ability and antibacterial ability is prepared.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing a bone-promoting antibacterial biological functional material comprises the following steps:
[0008] Step 1, ultrasonically treating and drying the polished nickel-titanium alloy material;
[0009] Step 2, focusing the femtosecond laser vertically onto the surface of the nickel-titanium alloy material;
[0010] Step 3: The femtosecond laser and the nickel-titanium alloy generate relative motion, and the processing is repeated along the same motion path to obtain a groove structure of a self-organized composite periodic microwave ripple;
[0011] Step 4: placing the groove structure prepared in step 3 into an electrolytic cell for anodization treatment to form abundant nanopores on the groove structure, thereby obtaining a three-level micro-nano composite structure of groove-microripple-micropore;
[0012] Step 5: placing the three-level micro-nano composite structure prepared in step 4 into an alkaline Tris buffer solution containing dopamine hydrochloride to form a polydopamine coating on the three-level micro-nano composite structure to obtain a composite structure;
[0013] Step 6: Place the composite structure obtained in step 5 into a silver nitrate solution to obtain a bone-promoting and antibacterial biofunctional material.
[0014] The specific implementation steps of step three are as follows:
[0015] (1) Fixing the clean nickel-titanium alloy material on a glass slide, and then fixing the glass slide on a high-precision six-degree-of-freedom translation stage;
[0016] (2) Set the repetition rate of the femtosecond laser to 1000 Hz and use a 5x objective lens to focus the femtosecond laser on the surface of the material; control the laser flux to 1 J / cm 2 ~10J / cm 2 The processing speed is 500um / s-2000um / s, and the processing spacing is 8um-20um. The high-precision six-degree-of-freedom translation stage is controlled by a computer control system to make the sample move relative to the laser to obtain a groove structure.
[0017] The method of anodizing treatment described in step 4 is: prepare an electrolyte composed of sodium chloride, deionized water and ethylene glycol, connect the groove structure of the composite periodic microwave ripple prepared in step 3 to the working electrode of the electrochemical workstation, set the voltage of the electrochemical workstation to 5V-10V in constant current mode, and set the anodizing time to 180s-600s.
[0018] The specific implementation steps of step five are as follows: prepare a dopamine hydrochloride solution with a concentration of 1 mg / ml to 3 mg / ml, the solvent is an alkaline Tris buffer, the concentration is 10 mM to 50 mM, and the pH value is 8 to 10; and immerse the three-level micro-nano composite structure prepared in step four in the dopamine hydrochloride solution for 12h-24h, followed by ultrasonic cleaning and vacuum drying.
[0019] The specific implementation steps of step six are as follows: prepare a silver nitrate solution with a concentration of 10mM-50mM, place the composite structure prepared in step five into the silver nitrate solution, and react for 1h-12h; then ultrasonically clean and dry.
[0020] The obtained bone-promoting antibacterial biological functional material is used for bone defect repair and postoperative bacterial infection; the obtained bone-promoting antibacterial biological functional material has the function of resisting bacterial infection and promoting bone defect repair.
[0021] Beneficial effects:
[0022] 1. The bone-promoting and antibacterial biological functional material and its preparation method of the present invention utilize femtosecond laser and nickel-titanium alloy material to generate relative motion and have the ability of patterning processing, and can be used for nickel-titanium alloy materials of various sizes and shapes.
[0023] 2. A bone-promoting antibacterial biofunctional material and a preparation method thereof of the present invention, the prepared biofunctional material can effectively inhibit the formation of biofilm, has a certain anti-bacterial adhesion ability through the multi-level micro-nano composite structure and significantly kills a variety of bacteria adhering to the surface through the surface silver element, and has excellent anti-bacterial infection ability. At the same time, the biofunctional material has excellent cell compatibility in vitro, is non-cytotoxic and can significantly induce bone regeneration. It can be used to prevent bacterial infection, promote bone defect repair, and improve the problem of poor bone integration of bone implants.
[0024] 3. The present invention provides a bone-promoting and antibacterial biofunctional material and a preparation method thereof. The prepared groove-micro-ripple-micropore three-level micro-nano composite structure has excellent drug loading capacity. The groove-micro-ripple-micropore three-level micro-nano composite structure with high specific surface area can provide abundant drug loading space to increase the drug loading amount.
[0025] 4. The present invention provides a bone-promoting and antibacterial biofunctional material and a preparation method thereof. The preparation method of the groove-microripple-micropore three-level micro-nano composite structure biofunctional material is flexible and simple, the process parameters are easy to control, and it is easy to realize application in the field of laser technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a light path diagram of the processing method of the present invention.
[0027] Figure 2 The following are SEM images of materials prepared by the implementation examples of the present invention. (a) is a SEM image of the groove-micro-corrugation composite structure prepared by femtosecond laser processing and polishing nickel-titanium alloy; (b) is a SEM image of the groove-micro-corrugation-micropore three-level micro-nano composite structure prepared by anodizing the sample after femtosecond laser processing; (c) is a SEM image of the groove-micro-corrugation-micropore three-level micro-nano composite structure after loading antibacterial nanosilver.
[0028] Figure 3 These are the test results of the surface contact angles of various types of materials prepared in the embodiments of the present invention.
[0029] Figure 4 It is the cytotoxicity of the bone-promoting and antibacterial biological functional material prepared in the embodiment of the present invention.
[0030] Figure 5 This is a fluorescence microscopic image of osteoblasts (MC3T3-E1, after 24 hours of co-culture) of the bone-promoting antibacterial biofunctional material prepared in the embodiment of the present invention. Among them, (a) is the survival of osteoblasts on the surface of clean polished nickel-titanium alloy; (b) is the survival of osteoblasts on the surface of groove-micro-corrugated composite structure prepared by femtosecond laser processing and polishing nickel-titanium alloy; (c) is the survival of osteoblasts on the groove-micro-corrugated-micropore three-level micro-nano composite structure prepared by anodizing the sample after femtosecond laser processing; (d) is the survival of osteoblasts on the surface of groove-micro-corrugated-micropore three-level micro-nano composite structure after loading antibacterial nanosilver.
[0031] Figure 6The fluorescence microscopic images of osteoblasts (MC3T3-E1, after 24 hours of co-culture) adhered to the bone-promoting antibacterial biofunctional material prepared in the embodiment of the present invention. Among them, (a) is the adhesion of osteoblasts on the surface of clean and polished nickel-titanium alloy; (b) is the adhesion of osteoblasts on the surface of groove-micro-corrugated composite structure prepared by femtosecond laser processing and polishing nickel-titanium alloy; (c) is the adhesion of osteoblasts on the groove-micro-corrugated-micropore three-level micro-nano composite structure prepared by anodizing the sample after femtosecond laser processing; (d) is the adhesion of osteoblasts on the surface of groove-micro-corrugated-micropore three-level micro-nano composite structure after loading antibacterial nanosilver.
[0032] Figure 7 The fluorescence microscopic images of Staphylococcus aureus colonization on the bone-promoting antibacterial biofunctional material prepared by the embodiment of the present invention. (a) shows the colonization of Staphylococcus aureus on the surface of the clean and polished nickel-titanium alloy; (b) shows the colonization of Staphylococcus aureus on the surface of the groove-micro-corrugated composite structure prepared by femtosecond laser processing and polishing nickel-titanium alloy; (c) shows the colonization of Staphylococcus aureus on the surface of the groove-micro-corrugated-micropore three-level micro-nano composite structure prepared by anodizing the sample after femtosecond laser processing;
[0033] (d) The colonization of Staphylococcus aureus on the surface of the groove-microripple-micropore three-level micro-nano composite structure after loading with antibacterial nanosilver.
[0034] Figure 8 The fluorescence microscopic images of Escherichia coli colonization on the bone-promoting antibacterial biofunctional material prepared by the embodiment of the present invention. Among them, (a) is the colonization of Escherichia coli on the surface of the clean and polished nickel-titanium alloy; (b) is the colonization of Escherichia coli on the surface of the groove-micro-corrugated composite structure prepared by femtosecond laser processing and polishing nickel-titanium alloy; (c) is the colonization of Escherichia coli on the groove-micro-corrugated-micropore three-level micro-nano composite structure prepared by anodizing the sample after femtosecond laser processing; (d) is the colonization of Escherichia coli on the surface of the groove-micro-corrugated-micropore three-level micro-nano composite structure after loading antibacterial nanosilver.
[0035] Among them, 1-femtosecond laser; 2-continuous attenuation plate; 3-first reflector; 4-second reflector; 5-light shutter; 6-third reflector; 7-focusing lens; 8-nickel-titanium alloy material to be processed; 9-six-degree-of-freedom translation stage; 10-dichroic mirror; 11-white light source; 12-CCD camera; 13-computer. DETAILED DESCRIPTION
[0036] The present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0037] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0038] Example 1
[0039] The present embodiment provides a bone-promoting antibacterial biofunctional material and a preparation method thereof, comprising the following specific steps:
[0040] Step 1: Clean the polished nickel-titanium alloy material with a surface roughness of less than 5 angstroms using an ultrasonic cleaner. Immerse the sample in deionized water and anhydrous ethanol solution at room temperature, respectively. Set the ultrasonic frequency of the ultrasonic cleaner to 80 kHz and clean for 5 minutes.
[0041] Step 2: Blow dry the cleaned sample described in step 1 with an ear bulb to obtain a clean nickel-titanium alloy sample.
[0042] Step 3: Use Figure 1 The femtosecond laser processing system shown in the figure includes: 1-femtosecond laser; 2-continuous attenuation plate; 3-first reflector; 4-second reflector; 5-light shutter; 6-third reflector; 7-focusing lens; 8-nickel-titanium alloy material to be processed; 9-six-degree-of-freedom translation stage; 10-dichroic mirror; 11-white light source; 12-CCD camera and 13-computer; the laser light generated by the femtosecond laser sequentially passes through the continuous attenuation plate, the first reflector, the second reflector, the light shutter, the third reflector and the focusing lens, and is focused on the surface of the nickel-titanium alloy material to be processed; the computer controls the switching of the light shutter and the movement of the six-degree-of-freedom translation stage; the white light generated by the white light source sequentially passes through the dichroic mirror, the third reflector and the focusing lens to irradiate the surface of the nickel-titanium alloy material to be processed, and is sequentially reflected along the focusing lens, the third reflector and the dichroic mirror to the CCD camera to generate real-time imaging of the processing area. A groove-microripple micro-nano composite structure was prepared on the surface of nickel-titanium alloy. The laser processing parameters were specifically set as follows: the wavelength of the femtosecond laser was 800nm, the repetition frequency was 1kHz, the processing objective lens was a 5x objective lens, the processing was done at the focus, and the laser flux was 5.43J / cm 2 ,The scanning speed is 600μm / s, the scanning pitch is 10um, and high-pressure nitrogen is used to blow chips during the entire processing process to produce a large-area, consistent groove-micro-ripple micro-nano composite structure;
[0043] Step 4: Anodize the sample prepared in step 3 using an electrochemical workstation, connect the platinum sheet and the sample prepared in step 3 to the counter electrode and the working electrode respectively, select a saturated calomel reference electrode, the anodizing electrolyte is an ethylene glycol solution containing 5.0 vol.% H2O and 0.3 M NaCl, the electrolysis voltage is 10 V, and the anodizing time is 5 min to prepare a three-level micro-nano composite structure of grooves-microripples-micropores.
[0044] Step 5: Place the groove-microripple-micropore three-level micro-nano composite structure prepared in step 4 into an alkaline Tris buffer containing dopamine hydrochloride, wherein the concentration of dopamine hydrochloride (DA) is 2 mg / mL, the pH of the Tris buffer is 8.5, and stand at room temperature for 24 hours.
[0045] Step 6: Place the groove-microripple-micropore three-level micro-nano composite structure with polydopamine coating prepared in step 5 into a silver nitrate solution, and use the reducing property of polydopamine to form nanosilver particles thereon, wherein the concentration of the silver nitrate solution is 50 mM and the reaction time is 6 hours.
[0046] Step 7: Rinse the groove-microripple-micropore three-level micro-nano composite structure material loaded with nanosilver particles prepared in step 6 with deionized water, and vacuum dry it in a vacuum drying oven (37° C., 4 h) to obtain the nickel-titanium alloy bone-promoting and antibacterial biofunctional material.
[0047] The product prepared by the method of the present invention has excellent anti-bacterial infection function, and the function of promoting bone integration and bone defect repair, and can be used in medical devices such as bone implants, for repairing bone defects and treating postoperative bacterial infections.
[0048] like Figure 1 Shown is the optical path diagram of the processing method of the present invention.
[0049] like Figure 2 Shown are SEM images of the surfaces of various types of materials prepared in the embodiments of the present invention.
[0050] like Figure 3 The static contact angles of various types of material surfaces prepared in the embodiments of the present invention are shown. From the figure, it can be seen that the contact angles of the original polished surface of nickel-titanium alloy (denoted as P-NiTi), the groove-micro-corrugated structure surface (denoted as Fs-NiTi), the groove-micro-corrugated-micropore three-level micro-nano composite structure surface (denoted as Fs-NPs), and the groove-micro-corrugated-micropore three-level micro-nano composite structure loaded nanosilver surface (denoted as Fs-NPs-PDA-Ag) are 72.6°±5.4°, 74°±10.1°, 36°±4.8°, and 41.5°±2.6°, respectively. After the sample surface after femtosecond laser processing and anodization treatment is coated with a polydopamine coating and loaded with nanosilver, it has a strong ability to adsorb water molecules, which reduces the surface contact angle to 41.5°±2.6°, and has good hydrophilicity.
[0051] like Figure 4The cell activity and proliferation test of the bone-promoting antibacterial biofunctional material prepared in the embodiment of the present invention is shown. Under the culture time of 1d, 3d, and 5d, there is basically no significant difference in the relative activity of each group of cells on the first day, and the cell activity is almost 100%. With the increase of incubation time, compared with the original surface, the cell proliferation rate of each group of samples treated increased significantly, indicating that femtosecond laser processing, anodizing treatment, and loading of antibacterial nanosilver have no obvious inhibitory effect on cell proliferation. The bone-promoting antibacterial biofunctional material has excellent biocompatibility and can promote cell proliferation to a certain extent.
[0052] like Figure 5 The figure shows the in vitro cell viability test of the bone-promoting and antibacterial biological functional materials prepared in the embodiments of the present invention. It can be seen from the fluorescence micrographs that the surfaces of the samples in each group in the embodiments of the present invention are all large-area green fluorescence, with basically no red fluorescence, and the cells in each group are basically alive, indicating that the prepared materials in each group are basically non-cytotoxic.
[0053] like Figure 6 The figure shows the bone regeneration induction characteristics of the bone-promoting antibacterial biofunctional material prepared in the embodiment of the present invention. It can be seen from the fluorescence microscopy image that compared with the original polished surface ( Figure 6 (a) Osteoblasts with abundant pseudopodia almost completely cover the surface of the groove-microripple-micropore three-level micro-nano composite structure ( Figure 6 (c)) and groove-microripple-micropore three-level micro-nano composite structure loaded with nanosilver surface ( Figure 6 (d)), and the number of cells also increased significantly compared with the original polished surface, indicating that the bone-promoting and antibacterial biofunctional material prepared in the embodiment of the present invention can significantly induce the adhesion and proliferation of osteoblasts and has excellent osteogenic properties.
[0054] like Figure 7 The fluorescent microscopic image of Staphylococcus aureus colonization on the bone-promoting antibacterial biofunctional material prepared in the embodiment of the present invention is shown. Figure 7 (a) The coverage of live bacteria (green) is 38.9%, and the coverage of dead bacteria (red) is 0.01%. Staphylococcus aureus colonizes almost the entire sample surface and almost no bacteria die. Groove-micro-corrugated surface ( Figure 7 (b) The coverage of live bacteria (green) is 31.4%, and the coverage of dead bacteria (red) is 0.1%. The number of Staphylococcus aureus has decreased. Groove-microripple-micropore three-level micro-nano composite structure surface ( Figure 7(c)) The coverage of live bacteria (green) is 15.8%, and the coverage of dead bacteria (red) is 1.2%. It is observed that the number of Staphylococcus aureus is lower than that of the original surface, indicating that the groove-micro-corrugation-micropore three-level micro-nano composite structure has greatly reduced the colonization sites of Staphylococcus aureus. Groove-micro-corrugation-micropore three-level micro-nano composite structure loaded with nanosilver surface ( Figure 7 (d)) The live bacteria (green) coverage on the surface was 0.1%, the dead bacteria (coverage) was 2.3%, and there was almost no live S. aureus colonization.
[0055] like Figure 8 The fluorescent microscopic image of Escherichia coli colonization on the bone-promoting antibacterial biofunctional material prepared in the embodiment of the present invention is shown. Figure 8 (a) The coverage of live bacteria (green) is 49.9%, and the coverage of dead bacteria (red) is 0.1%. The surface is evenly covered with E. coli. Groove-micro-corrugated surface ( Figure 8 (b) The coverage of live bacteria (green) is 38.9%, and the coverage of dead bacteria (red) is 0.4%, and the number of E. coli colonization has been reduced to a certain extent. Groove-microripple-micropore three-level micro-nano composite structure surface ( Figure 8 (c)) The coverage of live bacteria (green) is 20.6%, and the coverage of dead bacteria (red) is 0.3%. The groove-micro-corrugation-micropore three-level micro-nano composite structure greatly reduces the number of E. coli colonization, indicating that the structure has the effect of resisting E. coli colonization. The groove-micro-corrugation-micropore three-level micro-nano composite structure loaded with nanosilver surface ( Figure 8 (d)) The coverage of live bacteria (green) is 0.1%, and the coverage of dead bacteria (red) is 2.1%. The number of E. coli on the surface is extremely small, and there is almost no live E. coli colonization.
[0056] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not limited to the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a bone-promoting antibacterial biological functional material, characterized by: The steps include: Step 1, ultrasonically treating and drying the polished nickel-titanium alloy material; Step 2, focusing the femtosecond laser vertically onto the surface of the nickel-titanium alloy material; Step 3: The femtosecond laser and the nickel-titanium alloy generate relative motion, and the processing is repeated along the same motion path to obtain a groove structure of a self-organized composite periodic microwave ripple; Step 4: placing the groove structure prepared in step 3 into an electrolytic cell for anodization treatment to form abundant nanopores on the groove structure, thereby obtaining a three-level micro-nano composite structure of groove-microripple-micropore; Step 5: placing the tertiary micro-nano composite structure prepared in step 4 into an alkaline Tris buffer solution containing dopamine hydrochloride to form a polydopamine coating on the tertiary micro-nano composite structure to obtain a composite structure; Step 6: Place the composite structure obtained in step 5 into a silver nitrate solution to obtain a bone-promoting and antibacterial biofunctional material.
2. The method for preparing a bone-promoting antibacterial biological functional material according to claim 1, characterized in that: The specific implementation steps of step three are as follows: (1) Fixing the clean nickel-titanium alloy material on a glass slide, and then fixing the glass slide on a high-precision six-degree-of-freedom translation stage; (2) Set the repetition rate of the femtosecond laser to 1000 Hz and use a 5x objective lens to focus the femtosecond laser on the surface of the material; control the laser flux to 1 J / cm 2 ~10J / cm 2 The processing speed is 500um / s-2000um / s, and the processing spacing is 8um-20um; the high-precision six-degree-of-freedom translation stage is controlled by a computer control system to make the sample move relative to the laser; and a groove structure of a composite periodic microwave ripple is obtained.
3. The method for preparing a bone-promoting antibacterial biological functional material according to claim 1, characterized in that: The method of anodizing treatment described in step 4 is: prepare an electrolyte composed of sodium chloride, deionized water and ethylene glycol, connect the groove structure of the composite periodic microwave ripple prepared in step 3 to the working electrode of the electrochemical workstation, set the voltage of the electrochemical workstation to 5V-10V in constant current mode, and set the anodizing time to 180s-600s.
4. The method for preparing a bone-promoting antibacterial biological functional material according to claim 1, characterized in that: The specific implementation steps of step five are as follows: prepare a dopamine hydrochloride solution with a concentration of 1 mg / ml to 3 mg / ml, the solvent is an alkaline Tris buffer, the concentration is 10 mM to 50 mM, and the pH value is 8 to 10; and immerse the three-level micro-nano composite structure prepared in step four in the dopamine hydrochloride solution for 12h-24h, followed by ultrasonic cleaning and vacuum drying.
5. The method for preparing a bone-promoting antibacterial biological functional material according to claim 1, characterized in that: The specific implementation steps of step six are as follows: prepare a silver nitrate solution with a concentration of 10mM-50mM, place the composite structure prepared in step five into the silver nitrate solution, and react for 1h-12h; then ultrasonically clean and dry.
6. The method for preparing a bone-promoting antibacterial biological functional material according to claim 1, characterized in that: The obtained bone-promoting antibacterial biological functional material is used for bone defect repair and postoperative bacterial infection; the obtained bone-promoting antibacterial biological functional material has the function of resisting bacterial infection and promoting bone defect repair.
7. A device for implementing the method according to any one of claims 1 to 6, characterized in that: include: Femtosecond lasers; Continuous attenuation sheet; a first reflecting mirror; a second reflecting mirror; Light shutter; A third reflector; Focusing lens; Nickel-titanium alloy material to be processed; Six-degree-of-freedom translation stage; dichroic mirror ; White light source; CCD camera and computer; the laser light generated by the femtosecond laser passes through a continuous attenuation plate, a first reflector, a second reflector, a light shutter, a third reflector and a focusing lens in sequence, and is focused on the surface of the nickel-titanium alloy material to be processed; the computer controls the switch of the light shutter and the movement of the six-degree-of-freedom translation stage; the white light generated by the white light source passes through a dichroic mirror, a third reflector and a focusing lens in sequence, and is irradiated onto the surface of the nickel-titanium alloy material to be processed, and is reflected along the focusing lens, the third reflector and the dichroic mirror in sequence to the CCD camera to generate real-time imaging of the processing area.
Citation Information
Patent Citations
Preparation method of titanium oxide nano-tube array-silver composite coating material
CN104131325A
Titanium alloy containing antibacterial coating as well as preparation method and application thereof
CN104357814A
Method for preparing micro-nano composite structure on surface of titanium substrate
CN105624763A
Method for preparing nano-silver antimicrobial coating on surface of biomedical metal
CN107115559A
Pyrolytic carbon surface self-organizing three-level micro-nano composite structure
CN114473212A